Measuring the impact of lean construction practices on project duration and variability: A simulation-based study on residential buildings - Erol, Huseyin; Dikmen, Irem; Birgonul, Talat (Journal of Civil Engineering and Management, 2017)
Performance of the construction projects have been criticized for many years due to their low productivity rates and cost overruns as well as significant delays. Increasing number of dissatisfied customers compel practitioners to reform conventional practices of construction management. Lean construction has emerged as a result of these efforts in the industry. However, there are limited number of studies that demonstrate the practical benefits of lean construction applications. The aim of this paper is to untangle practical applications of lean construction and to reveal their benefits. A methodology was developed to compare the lean and non-lean scenarios of a residential building project by means of Monte Carlo simulation. Simulation models were generated through regular meetings held with construction planning experts. Research findings demonstrate that application of lean construction principles have a potential to improve the performance of projects by reducing both the total project duration and its expected variation. In addition, the study revealed that utilization of practical lean construction principles may result in a considerable amount of time reduction in wall construction and plastering activities of residential building projects. Although the findings of this study cannot be generalized, they are expected to encourage practitioners to adopt lean construction principles.First published online: 24 May 2016